Hypertension Impact on Health-Related Quality of Life: A Cross-Sectional Survey among Middle-Aged Adults in Chongqing, China - Xianglong Xu; Yunshuang Rao; Zumin Shi; Lingli Liu; Cheng Chen; Yong Zhao (International Journal of Hypertension)
Hypertension is a major risk factor of cardiovascular disease in China, and yet little is known about health-related quality of life (HRQOL) and its associations with demographic and social-economic characteristics in middle-aged patients with hypertension. A cross-sectional survey was undertaken in Chongqing, China, using a multistage stratified random sampling methodology. Data was collected on 1,224 eligible adults, aged between 45 and 53 years, including the Medical Outcomes Survey Short Form-36 to measure HRQOL. Hypertension was associated with poor state of physical functioning, role-physical, bodily pain, general health, vitality, and social function (p<0.05 for all). In multivariable analyses, education level, job conditions, average monthly income, smoking status, sleep quality, perception of relationship with family, childhood breastfeeding history, and body mass index were associated with domains of SF36 among those with hypertension (p<0.05 for all). Hypertensive respondents with high education, marital status, breastfeeding, higher incomes, good quality of sleep, positive relationship with family, and higher body mass index have better HRQOL in middle-aged people with hypertension. Those unemployed had a better state of general health and had a poorer state of social function. Nonsmokers had a poorer state of bodily pain than smokers. This study provides detailed information of the implications for health care providers to gain a more complete picture of their hypertension patients’ health.